Northward Growth of the West Kunlun Mountains: Insight From the Age–Elevation Relationship of New Apatite Fission Track Data - Liu, Dongliang; Li, Haibing; Ge, Chenglong; Bai, Mingkun; Wang, Yadong; Pan, Jiawei; Zheng, Yong; Wang, Ping; Liu, Fucai; Wang, Shiguang (Frontiers in Earth Science, 2021)
The Cenozoic collision between India and Asia promoted the widespread uplift of the Tibetan Plateau, with significant deformation documented in the Pamir Plateau and West Kunlun Mountains. Low-temperature thermochronology and basin provenance analysis have revealed three episodes of rapid deformation and uplift in the Pamir–West Kunlun Mountains during the Cenozoic. However, there is very little low-temperature thermochronology age–elevation relationship (AER) data on fast exhumation events in this area—especially in the West Kunlun Mountains— leading to uncertainty surrounding how these events propagated within and around the mountain range. In this study, we produced an elevation profile across granite located south of Kudi, Xijiang Province, China, to reveal its exhumation history. Apatite fission track AER data show that a rapid exhumation event occurred at ∼26 Ma in the southern West Kunlun Mountains. When combined with published data, we interpret that the initial uplift events related to the India–Asia collision began in the central Pamir, southern West Kunlun, and northern West Kunlun regions during the Late Eocene, Oligocene, and Middle Miocene periods, respectively. Therefore, the Cenozoic northward growth process occurred from south to north around West Kunlun.